THE COLLAPSE OF THE DOFASCO NO. 2 ORE BRIDGE, MARCH 28th 1995, HAMILTON, ONTARIO - Verhey, Timothy (My University, 1995)
Dofasco started producing steel on their Hamilton bayfront property around 1952. Much of the iron ore and coal required for their blast furnace operations was delivered by ship. Two Ore Bridges, probably fabricated in 1951 and in continuous service since, were used to unload the ships.
On Tuesday March 28th, 1995 at approximately 8:40am, the No.2 Ore Bridge collapsed.
At the time, the Ore Bridge appeared to be stationary. The operator was also not performing any specified operation. The collapse initiated with the failure of the tie-plate which keeps the Shear Leg from spreading at its base. The tie-plate is a critical member. As the structure contained no reasonable alternative load path for the tension in the tieplate, the failure of the tie-plate resulted in the collapse of the Ore Bridge.
Initial calculations indicated there was no obvious structural overload that should have precipitated the catastrophic failure of the tie-plate. A metallurgical investigation of the tie-plate material was then initiated.
The metallurgical investigation found the steel in the tie-plate was susceptible to brittle fracture at the approximate air temperature at the time of the collapse. Using a fracture mechanics approach it was concluded the failure of the tie-plate was the consequence of fatigue cracks initiating in corrosion pits on the underside of the plate, along the toe of the reinforcing fillet weld connecting the tie-plate to the rocker block. The fatigue cracks grew and combined until they created a flaw which reached a critical dimension, allowing a brittle fracture to initiate and run rapidly across the width of the plate.
Over the years, the Ore Bridges have seen several alterations which increased the tension load in the tie-plate. In 1968 the apron was extended. In 1975 the trolley payload was increased. In 1990, increases in dead weight on the main span were recognised.
In 1990 however, Dofasco also modified their method of handling iron ore pellets on the bayfront, which required the addition of a hopper into the Shear Leg of the Ore Bridges. The addition of the hopper was critical, as it created unbalanced lateral loadings on the sill truss which were cyclical in nature. The hopper forced the tie-plate to resist these lateral loads by bending horizontally, a loading condition for which it was not originally designed. The cyclic bending stresses resulting from the addition of the hopper led directly to the failure of the tie-plate and the resulting collapse of the No.2 Ore Bridge.
Keywords: dofasco; ore bridge; Hamilton; Ontario